Does Poverty Research in Russia Follow the Scientific Method? - Lokshin, Michael (World Bank, Washington, DC, 2012)
This paper presents the first critical review of literature on poverty published in Russia between 1992 and 2006. Using a dataset of about 250 publications in Russian scientific journals, the authors assess whether the poverty research in Russia satisfies the general criteria of a scientific publication and if such studies could provide reliable guidance to the Russian government as it maps out its anti-poverty policies. The findings indicate that only a small proportion of papers on poverty published in Russia in 1992-2006 follow the universally-recognized principles of the scientific method. The utility of policy advice based on such research is questionable. The authors also suggest steps that could, in their view, improve the quality of poverty research in Russia.